Chemical Composition and Effect of Feeding Different Levels of Sugarcane Tops with Concentrate Mixture/ Mustard Cake on Digestibility in Buffalo Calves - Sharma, Vijay Kumar; Tomar, S K; Kundu, S S; Jain, Pankaj; Jha, Pankaj; Kumar, Muneendra; Lata, Manju (Indian Journal of Dairy Science, 2012)
The present study was conducted to evaluate the nutritive value of the sugarcane tops (SCT) of the elite clones as fodder. Initially proximate analysis of the 28 varieties of the SCT for the three cuts was done and the variety no. CoJ-64 was found to have highest crude protein content. The total gas content of the different varieties varied between 31.8 to 56.2 ml, 29.25 to 55.1 ml, 28.75 to 54.5 ml for 1st (early), 2nd (mid) and 3rd (late) harvesting stage cut respectively and there was significant difference (p<0.05) between means of different cuts and varieties. Sixteen Murrah buffalo calves of similar age and body weight were divided into four groups randomly of four animals each. The group 1 was fed with 100% SCT (control) and in group 2, 3, 4, the SCT was replaced by 20%, 30%, and 40% concentrate mixture respectively. After an adaptation period of 21 days on experimental diet, the 1st digestibility trial was conducted. The DM, CP, EE, ADF, NDF, OM digestibility was higher (p<0.01) in the 3rd and 4th group as compared to the 1st group owing to the higher DCP and TDN in the 3rd and 4th group. In the 2nd trial the same animals were used and divided into four groups randomly of four animals in each group. The group 1 was fed with 100% SCT and in group 2, 3 and 4 th SCT was replaced by 20, 30, 40 % mustard cake to match the field conditions. The DM, CP, EE, ADF, NDF, OM digestibility was higher (p<0.01) in the 3rd and 4th group as compared to the 1st group owing to the higher DCP and TDN in the 3rd and 4th group. In both the trials there was no significant difference found in 1st and 2nd group of animals.